Establishing Detection Methods for Okadaic Acid Aptamer–Target Interactions: Insights from Computational and Experimental Approaches - Wenchong Shan; Jiefang Sun; Runqing Liu; Jing Wang; Bing Shao (Foods)
The binding interactions between okadaic acid (OA) aptamers and OA molecules are crucial for developing effective detection methods. This study aims to identify the recognition site and establish a reliable detection protocol through computational simulations and experimental validations. After determining the target sequence (OA-2), molecular docking simulations using Sybyl-X and H-dock were conducted to predict the binding affinity and interaction sites of OA aptamers with their targets. These predictions were subsequently validated through experiments based on the Förster resonance energy transfer (FRET) principle. The combined approach not only confirmed the computational predictions, identifying the “major region” as the recognition basis of OA-2, but also provided deeper insights into the binding mechanisms. Subsequently, a classical AuNPs-aptamer colorimetric detection method was established based on the OA-2 sequence and applied to the detection of real shellfish samples, achieving a limit of quantification (LOQ) of 5.0 μg kg−1. The recoveries of OA in spiked samples ranged from 79.0% to 122.9%, with a relative standard deviation (RSD) of less than 14.7%. The results of this study contribute to the development of robust detection methods for OA aptamer–target interactions, enhancing the potential for practical applications in toxin detection and monitoring.